Design of Box Culvert in Iraqi Highways Considering Catchment Areas - Adil Jasim, Nidaa; ., . (International Journal of Engineering and Technology, 2018)
In Iraq, the infrastructures are developing rapidly, so it is necessary to consider the hydrology of the developed catchment before constructing any drainage facilities such as culvert to prevent traffic disruption during rain. In this study, sizing of box culvert for highways in Iraq is proposed using rational method for determination of peak runoff from small catchment (less than 3 km2). Rainfall depth was used to derive the intensity duration frequency curve, and then the rainfall intensity was found. However, soil conservation service curve number (SCS-CN) was used in the estimation of peak runoff from catchment with size ranging from 3 to less than 30 km2 using the soil classification and the curve number.Â HY-8 computer software was used for sizing square and circular sections. Circular sections were also calculated. The appropriate sizes for square sections in large basins are 3 m to 4 m and 2 m to 2.9 m for more than 114 m3/s and 32 m3/s respectively, but for circular sections, diameters were 4.1m, from 3 m to 3.8 m and from 2.5 m to 2.9 m under flow rates more than 160 m3/s, 68 m3/s and 25 m3/s respectively. However, for small basins, square sections sizes were 3m to 3.1m and 2 m to 2.7 m for flow rates more than 23 m3/s and 8 m3/sÂ respectively. Diameters for circular sections were 3 m to 3.2 m and 2 m to 2.9 m under flow rates 23 m3/ s and 8 m3/s respectively.Â Â Â